EA Ameliorated Depressive Behaviors in CUMS Rats and Was Related to Its Suppressing Autophagy in the Hippocampus. (22nd September 2020) - Zhang, Zhinan; Cai, Xiaowen; Yao, Zengyu; Wen, Feng; Fu, Zhiyi; Zhang, Jiping; Zhong, Zheng; Huang, Yong; Qu, Shanshan
Abstract : Autophagy is confirmed to be involved in the onset and development of depression, and some antidepressants took effect by influencing the autophagic process. Electroacupuncture (EA), as a common complementary treatment for depression, may share the mechanism of influencing autophagy in the hippocampus like antidepressants. To investigate that, sixty Sprague-Dawley rats firstly went through chronic unpredictable mild stress (CUMS) model establishment, and 15 rats were assigned to a control group. After modeling, 45 successfully CUMS-induced rats were randomly divided to 3 groups: CUMS, selective serotonin reuptake inhibitor (SSRI), and EA groups (15 rats per group), to accept different interventions for 2 weeks. A sucrose preference test (SPT), weighing, and open field test (OFT) were measurement for depressive behaviors of rats. Transmission electron microscope (TEM), immunohistochemistry (IHC), and western blot analysis were used to evaluate the autophagic changes. After that, depression-like behaviors were successfully induced in CUMS models and reversed by SSRI and EA treatments (both p < 0.05 ), but these two therapies had nonsignificant difference between each other (p > 0.05 ). Autolysosomes observed through TEM in the CUMS group were more than that in the control group. Their number and size in the SSRI and EA groups also decreased significantly. From IHC, the CUMS group showed enhanced positive expression of both Beclin1 and LC3 in CA1 after modeling (p < 0.05 ), and the LC3 level declined after EA treatments, which was verified by decreased LC3-II/LC3-I in western blot analysis. We speculated that CUMS-induced depression-like behavior was interacted with an autophagy process in the hippocampus, and EA demonstrated antidepressant effects by partly inhibiting autophagy with a decreased number of autolysosomes and level of LC3 along with LC3-II/LC3-I.